The Role of The Kurdistan Parliament in Protecting the Rights of Minorities: A Comparative Analytical Study - Mariwan Saber Hamad; Kale Wsu Ahmed (QALAAI ZANIST JOURNAL, 2022)
This study analyzes the role of the Parliament of the Kurdistan Region in protecting the rights of the minorities. The law on the protection of the rights of minorities in Kurdistan - Iraq No. (5) of (2015) is the culmination of many laws that have been enacted by Parliament since its establishment until now, which are related to the protection of political, economic, social and cultural rights for all minorities of the Kurdistan Region, and we have studied In this study to address the legal problems related to ensuring that the minorities exercise their rights mentioned in the laws in force, and to present recommendations and proposals related to the subject of the study for the purpose of amending some legal texts in line with developments in the Kurdistan Region - Iraq. We discussed the political representation of the minorities in the Parliament of the Kurdistan Region, where we studied on the texts of the Kurdistan Parliament Election Law No. (1) for the year (1992) related to the allocation of certain seats to components in the region, and our evaluation of this organization in light of international standards for the political participation of minorities, and we have studied the legislative role of Parliament and its contribution to protecting the rights of minorities